2019
DOI: 10.1007/s00338-019-01788-7
|View full text |Cite
|
Sign up to set email alerts
|

Coral bleaching and recovery from 2016 to 2017 at East and West Flower Garden Banks, Gulf of Mexico

Abstract: East Flower Garden Bank (EFGB) and West Flower Garden Bank (WFGB), part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwestern Gulf of Mexico, support tropical coral reefs that exhibit over 50% living coral cover. These reefs have been monitored annually since 1989, and in 2016 were exposed to higher than normal seawater temperatures leading to a severe bleaching event. Corals at EFGB and WFGB showed no signs of bleaching until September 2016, occurring later in the year compared to othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…In some cases, local conditions like upwelling (Riegl et al 2019) or high turbidity (Morgan et al 2017;Teixeira et al 2019) may help corals survive, while local growth of fleshy algae may increase bleaching susceptibility (Smith et al 2019). In others, reefs may be predominated by a few species that are resilient to bleaching and recover well (Johnston et al 2019) but may have reduced reproductive output or success (Fisch et al 2019;Hughes et al 2019b). Repeated years of heat stress may result in less bleaching during later events (Harrison et al 2018;Fisch et al 2019;Hughes et al 2019a) or may overwhelm reefs to the point that their persistence is in question (Riegl et al 2018;Raymundo et al 2019).…”
Section: What Have We Learned From Gcbe-3?mentioning
confidence: 99%
“…In some cases, local conditions like upwelling (Riegl et al 2019) or high turbidity (Morgan et al 2017;Teixeira et al 2019) may help corals survive, while local growth of fleshy algae may increase bleaching susceptibility (Smith et al 2019). In others, reefs may be predominated by a few species that are resilient to bleaching and recover well (Johnston et al 2019) but may have reduced reproductive output or success (Fisch et al 2019;Hughes et al 2019b). Repeated years of heat stress may result in less bleaching during later events (Harrison et al 2018;Fisch et al 2019;Hughes et al 2019a) or may overwhelm reefs to the point that their persistence is in question (Riegl et al 2018;Raymundo et al 2019).…”
Section: What Have We Learned From Gcbe-3?mentioning
confidence: 99%
“…Depth was a significant factor for all environmental metrics, but site was only a significant factor affecting PAR metrics (Kruskal‐Wallis: all significant p < 0.002; Table ). During September 2016 (just prior to and during the 12 month timepoint), sea surface temperatures were >30°C, corresponding to a coral bleaching event observed at WFGB and EFGB (Johnston et al., 2019). All of the shallow controls and transplants at both sites exhibited some level of visible bleaching.…”
Section: Resultsmentioning
confidence: 99%
“…Perhaps the most interesting, yet unexpected, outcome of the transplant experiment was the opportunity to examine responses of transplanted corals following a thermal stress event. Previous monitoring efforts at WFGB and EFGB have demonstrated that temperatures of 29.5°C or greater for >50 days can cause bleaching events (Johnston et al., 2019). Mean daily temperatures at the shallower sites remained >30°C for at least 80 days through the 12 month timepoint (Figure ), resulting in widespread coral bleaching observed at the shallower depth zones of both WFGB and EFGB.…”
Section: Discussionmentioning
confidence: 99%
“…• Mean annual SST: an upper temperature limit for coral bleaching in the Pacific has been reported as 28.1 • C, but more recent work shows an increasing bleaching threshold of 28.7 • C (Sully et al, 2019). In the GoM, reported bleaching thresholds are higher, approaching 30-31 • C. Wilkinson and Souter (2008) found corals bleached in the Caribbean when SST reached 31 • C and were sustained; Florida Keys and Flower Garden Banks reefs bleach when SST reached 30-31 • C (Johnston et al, 2019b) or 29.5 • C if temperatures were sustained for 50 days (Johnston et al, 2019a). We consider mean annual SSTs approaching 30 • C as high risk for coral bleaching in the GoM.…”
Section: Defining Coral Reef Stress Factorsmentioning
confidence: 99%
“…At present, there is strong evidence that GoM reefs have experienced thermal stress since 1878 (Kuffner et al, 2015) with recent bleaching events in 2016/2017 (Johnston et al, 2019a). In situ SST records show a 0.8 • C increase over the last century in the Florida Keys, where corals have declined especially in the later part of the twentieth century.…”
Section: Introductionmentioning
confidence: 97%